Electrochemical and optical-based immunosensor for detection of Mycobacterium tuberculosis - Mohd Bakhori, Noremylia (2019)
Tuberculosis (TB) caused by Mycobacterium tuberculosis is a major obstacle for the global that effect the rate of morbidity and mortality. Many attempts and affords had been taken such as developing the drugs for controlling TB, curing the patients and preventing further transmission of the disease. Conventional diagnosis tool of TB often time-consuming, required loads of samples, less sensitive, impractical and costly for point of care diagnostic. In this research, a novel for diagnosis of TB was developed by an optical and electrochemical immunosensor via antibody-antigen interaction for the detection of TB-protein biomarker CFP10-ESAT6. For optical immunosensor, we studied a naked eye detection for TB by utilizing plasmonic enzyme-linked immunosorbent assay (ELISA) for the detection of protein biomarker, Mycobacterium tuberculosis ESAT-6-like protein esxB (CFP10-ESAT6). Here, the biocatalytic cycle of the intracellular enzymes,catalase links to the formation and successive growth of the gold nanoparticles (AuNPs). The formation of blue and red of AuNPs colored solutions links directly to the absence or presence of the TB analytes in the sample solutions. The immunoassay involves catalase-labeled antibodies which consume hydrogen peroxide for reduction of gold (III) chloride and further produce AuNPs. The fast rate of reaction determines the agglomerated of AuNPs for blue solutions while slow reaction for red solution which from monodispersed AuNPs. This serves as a conﬁrmation for the naked eye detection of TB analytes. The optimum concentration of H2O2 and gold ion were 150 µM and 0.25 mM respectively. In the presence of CFP10-ESAT6, blue color produced while in the absence of CFP10-ESAT6, red solution appeared. The detection limit (LOD) of- developed method was 0.01 µg/mL by the naked eye. Additionally, the plasmonic ELISA shows high specificity towards CFP10-ESAT6 protein compared with MPT64 and BSA. Furthermore, our developed technique was successfully tested and conﬁrmed with sputum samples from patients diagnosed with positive and negative TB with good reproducibility. The results show only positive TB sputum samples produced blue color solutions compared with negative sputum samples, non-tuberculosis Runyon Group IV and Mycobacterium fortuitum chelonae complex. The results provided enough evidence for the utilization of our technique in the early diagnosis of TB disease. For electrochemical immunosensor, a modified quantum dot with thioglycolic acid (TGA) (CdSe-ZnS QD) and functionalized silica nanoparticles (SiO2NPs) as modifiers were prepared to enhance performance of disposable screen printed carbon electrode (SPCE). CdSe-ZnS QD was characterized by using fluorescence spectroscopy and High Resolution Transmission Electron Microscopy (HRTEM) while SiNPs with Transmission Electron Microscopy (TEM) and Fourier Transform Infrared (FTIR). Functionalized SiO2NPs and CdSe-ZnS QD were dropped cast on the working electrode for preparation of CdSe-ZnS QD/ SiO2NPs/SPCE. Electrochemical studies using cyclic voltammetry (CV) performed with SiO2NPs/SPCE and CdSe-ZnS QD/SiO2NPs/SPCE were found to give a better response through the optimization of numerous analytical parameters. The modified SPCE was characterized using Field Emission Scanning Electron Microscope (FESEM) and Energy Dispersive X-ray (EDX) respectively. The CdSe-ZnS QD/SiO2NPs/SPCE modified electrode showed increment of active surface area with 4.14 folds higher than bare SPCE. Then indirect ELISA immunoassay was performed on the modified electrode for CFP10-ESAT6 detection using differential potential voltammetry (DPV). DPV current response increased in the presence of CFP10-ESAT6 while decreased in the absence of CFP10-ESAT6. Other than that, DPV current was high for CFP10-ESAT6 compared with BSA and MPT64. The detection of CFP10-ESAT6 showed a linear response towards 2 different concentration of CFP10-ESAT6 with R = 0.9487 for calibration curve. The detection limit of 3.3 x 10-11 g/mL was achieved for linear range of 20 to 100 ng/mL of CFP10-ESAT6 concentration. The proposed methods showed good selectivity and reproducibility of target analyte with RSD value of 1.45 %. As summary, the developed optical immunosensor utilized plasmonic ELISA marked as suitable quantitative method for naked eye detection of TB. Besides, the developed electrochemical immunosensor which used the fabricated electrode can be used as qualitative technique for TB.